2021
DOI: 10.3390/cancers13225604
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: Their Role in Metabolism, Tumor Microenvironment, and Therapeutic Implications in Head and Neck Squamous Cell Carcinoma

Abstract: MicroRNAs (miRNAs) are endogenous small non-coding RNA molecules that negatively regulate gene expression by binding to target mRNAs. Deregulated miRNAs can act as either oncogenic miRNAs or tumor suppressor miRNAs in controlling proliferation, differentiation, apoptosis, metastasis, epithelial–mesenchymal transition, and immune responses, which are all involved in the carcinogenesis process of HNSCC. Recent findings have shown that metabolic reprogramming is an important hallmark of cancer, which is necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 134 publications
0
12
0
Order By: Relevance
“…Given such intimacy between various miRNAs and GLUT isoforms, there is a strong logic to utilize them in therapeutic applications. Similarly, a study on the role of MiR-218 and MiR340 in the expression of GLUT1 is demonstrated in oral squamous cell carcinoma (OSCC) (Xu et al, 2018;Shiah et al, 2021). Combinatorial use of miRNAs with other conventional GLUT1 inhibitors is also needed to be explored to circumvent GLUT at both gene expression and protein function levels.…”
Section: Mirnas In Anti-glut Strategiesmentioning
confidence: 99%
“…Given such intimacy between various miRNAs and GLUT isoforms, there is a strong logic to utilize them in therapeutic applications. Similarly, a study on the role of MiR-218 and MiR340 in the expression of GLUT1 is demonstrated in oral squamous cell carcinoma (OSCC) (Xu et al, 2018;Shiah et al, 2021). Combinatorial use of miRNAs with other conventional GLUT1 inhibitors is also needed to be explored to circumvent GLUT at both gene expression and protein function levels.…”
Section: Mirnas In Anti-glut Strategiesmentioning
confidence: 99%
“…ncRNAs, including circular RNAs (circRNAs), microRNAs (miRNAs), and lncRNAs, interact with the components of the TME, thereby affecting tumorigenesis and progression (Table S1) (86)(87)(88). These ncRNAs, which are enriched in exosomes of CAFs, are transmitted to the cancer cells to regulate their biological characteristics.…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC), one of the most prevalent malignancies in the world, is a cancer of the squamous epithelium that lines the head and neck organs, such as the oral cavity, larynx, hypopharynx, oropharynx, nasopharynx, paranasal sinuses, nasal cavity, and salivary glands with poor outcomes and survival rates ( Shiah et al, 2021 ). However, palliative care is being considered as a systematic therapy for patients with recurrent or spread HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 10 years, it has been shown that microRNAs play an important role in the development of HNSCC cancer and its spread ( Qiu et al, 2021 ; Shiah et al, 2021 ; Yang et al, 2019 ; Yu et al, 2019 ). This makes them good candidates for biomarkers that can predict the biological activity of HNSCC.…”
Section: Introductionmentioning
confidence: 99%